System differential learning for detecting learning styles in science education for students with learning disabilities - Wibowo, Firmanul Catur; Nasbey, Hadi; Suprihatin, Suprihatin; Kusuma, Alfarizi Ade Karlin; Darman, Dina Rahmi; Costu, Bayram (Edelweiss Applied Science and Technology, 2024)
The research aims to develop a Differential System Learning (SIDILAN) effective for students to learn Disabilities (LD) in science learning. SIDILAN is designed to detect students' learning styles that suit their unique needs, especially those with difficulty understanding science concepts. The research method used is the ADDIE Model, an abbreviation for the five stages of the development process: Analysis, Design, Development, Implementation, and Evaluation. The implementation stage of ADDIE SIDILAN was implemented on 68 prospective teacher students in Indonesia aged 20-22 years, and they were then given a questionnaire to respond. The study results showed that the development of the SIDILAN online URL https://s.id/SIDILAN can be used to detect students' learning styles in science learning. Based on the student response questionnaire to SIDILAN for Learning Disability (LD), information was obtained that LD A for the Indicator of Understanding and Engagement was 84.31%, LD B for the Indicator of Effectiveness 87.25%, LD C for the Indicator of Skills and Self -Development of 92.65% and LD D for Indicator of Satisfaction and Recommendation of 95.59%. The findings indicate that SIDILAN effectively improves the quality of learning by offering personalized learning styles according to their needs, creating a more inclusive and supportive educational environment for students with learning disabilities. The study suggests that SIDILAN should be integrated into special education programs as an innovative solution to support the science learning process for students with special needs.